Bowel and bladder function in infant toilet training (BABITT) - protocol for a randomized, two-armed intervention study - Terese Nilsson; Anna Leijon; Ulla Sillén; Anna-Lena Hellström; Barbro Hedin Skogman (BMC, 2022)
Abstract Background In the last decades, the average age for toilet training has increased in the western world. It is suggested that the postponed initiation of toilet training is a contributing factor to problems related to bowel and bladder control. Functional gastrointestinal and urinary tract disorders are prevalent in childhood, causing suffering in affected children and for their families, and consuming healthcare resources. To evaluate whether assisted infant toilet training can prevent functional gastrointestinal and urinary tract disorders in young children, we are conducting a randomized intervention study with a 4-year follow-up. Methods This randomized two-armed intervention study will include 268 Swedish infants recruited at six child healthcare centers in Region Dalarna located in the central part of Sweden. The intervention entails parents being instructed and practicing assisted infant toilet training with their child. Children are randomized to start assisted infant toilet training at 0-2 months or at 9-11 months of age. The primary objective is to determine the efficacy of assisted infant toilet training initiated at 0-2 months on the prevalence of functional gastrointestinal disorders (defined as infant colic, infant dyschezia and/or functional constipation) up to the age of 9 months. Secondary objectives are to evaluate whether assisted toilet training initiated during the first year of life reduce the prevalence of functional gastrointestinal disorders (defined as functional constipation, gastrointestinal symptoms and/or stool toileting refusal) and urinary tract disorders (defined as bladder dysfunction and/or urinary tract infections) up to the age of 4 years. Furthermore, infant-to-mother attachment, parental stress, the toilet training process and overall parental experiences will be evaluated/explored. Discussion This protocol article presents the rationale and design of a randomized two-armed intervention study that will determine the efficacy of assisted infant toilet training on functional gastrointestinal disorders up to the age of 9 months. Furthermore, the study will evaluate whether assisted infant toilet training during the first year of life can prevent functional gastrointestinal and urinary tract disorders in children up to 4 years of age. If effective, assisted infant toilet training could be recommended in child healthcare settings and new evidence-based guidelines on infant toilet training could be implemented. Trial registration The study protocol was retrospectively registered at ClinicalTrials. gov  ( NCT04082689 ), initial release June 12th, 2019)